The impact of digital tools on curriculum delivery in public and private secondary schools in Awka south local government area - Nkolika, Chukwuka Judith (Bulletin of Educational Management and Innovation, 2025)
Background: With the increasing reliance on technology in education, it is crucial to assess how these tools enhance or hinder teaching effectiveness. This is because, integration of digital tools in education can transform curriculum delivery in secondary schools, influencing teaching methodologies and learning outcomes. Employing a descriptive correlational design, the study explored the extent of digital tool integration in teaching and its effects on curriculum delivery. Method: The sample consisted of 118 teachers from both public and private schools, selected using a purposive sampling technique. Data were collected through a structured questionnaire, which included both closed-ended and Likert-scale items, assessing the integration of digital tools and teachers' perceptions of their effectiveness. The questionnaire was administered via an online survey for accessibility and timely data collection. Statistical analysis, including regression analysis, was used to determine the relationships between variables such as school location, school type, and gender, and their effects on the use of digital tools. Findings: Results indicated that while school location significantly influenced digital tool integration, there is a moderate use of digital tools in lesson delivery (mean: 3.41) and communication (mean: 3.03), but limited support for personalized learning (mean: 1.81). Digital tools enhance student engagement (mean: 3.02) and curriculum delivery (mean: 3.32). Regression analysis indicates that location (B = 2.806, t = 4.716, p < 0.001) significantly affects integration, while school type and gender do not. The findings highlight the importance of location in shaping digital tool utilization, offering valuable insights for policymakers and educators seeking to enhance curriculum delivery through technology.